ANALYSIS OF EXISTING APPROACHES TO ORGANIZING INDEPENDENT LEARNING IN PHYSICS FOR STUDENTS - Kamoliddin Anvarovich Raximov (Western European Studies, 2024)
This article analyzes the existing approaches to organizing independent learning in physics for students. Traditional, problem-based, modular, and electronic teaching methods are reviewed, highlighting their significance in the educational process. The role of innovative technologies and interactive approaches in enhancing the effectiveness of independent learning is emphasized
Keywords: Independent learning; physics; pedagogical approaches; problem-based learning